Learning to be critically reflective: exploring fiction writing and adult learning. Issue 2 (4th May 2018) - Gouthro, Patricia A.; Holloway, Susan M.
ABSTRACT: Many educators in adult, community and higher education contexts are concerned with fostering reflective learning amongst their students. This paper explores the concept of critical reflection and considers how engaging with fiction may be an innovative pedagogical approach to support critical learning opportunities. Drawing upon interviews with fiction writers, ways in which critical reflection may be encouraged in connection to reading and writing fiction are taken up by exploring three different thematic areas that relate to a Habermasian framework of knowledge constitutive approaches to learning. These different areas can be categorised as (a) technical-rational, (b) humanistic and (c) critical or emancipatory. The first of these considers critical reflection as a way to develop technical capacities as a creative writer. The next section takes up a humanistic framework to explore the value of individual and collective learning opportunities to enhance personal growth and critical reflection. The third area of discussion considers a deeper critical or emancipatory framework of learning through critical reflection which may lead to social change. The paper concludes by considering the value of arts-informed adult education approaches, such as those related to fiction writing, to enhance the development of critical reflection amongst adult learners.